Reception of Indian Culture and Art in the Comparative Studies of Enlightenment - Jaskūnas, Valdas (Acta Orientalia Vilnensia, 2002)
The article deals with the modes of reception of Indian art in the Western comparative studies of religion, mythology and art of the 18th century. While emphasizing the ambivalence of the epistemic paradigms formed by the ideas of Radical Enlightenment on the one hand, and Christian Reaction on the other, it can be seen that the modes of reception of Indian art have been serving as the particular simulacra attempted to confirm or to deny Eastern influences on Western civilization. Hence, knowledge of Indian art was drawn into the normative system of European culture and art and shortly became the basic reference in the cultural schemes of linear progress aiming to deny mostly Egyptian influence on Western civilization.